Epidemiological and Clinical Profile of Healthcare Providers Affected With Covid-19 at Civil Hospital; Medicity Campus; Ahmedabad; Gujarat - Kartikeya G Parmar; Dhaval V Parekh; Jinal Nogas; Bhagyalaxmi , Aroor; Devang Raval; Rajesh Solanki (National Journal of Community Medicine, 2021)
Background: SARS-CoV-2 has spread globally at a rapid pace, causing significant morbidity and mortality. Healthcare providers are especially vulnerable to infection with important implications. There might be adverse effects on their health, they could transmit the infection to vulnerable patients, family contacts and other staff if not quickly isolated and high rates of infection could cause problems due to health system manpower shortage.